2020
DOI: 10.1016/j.bj.2020.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric abusive head trauma

Abstract: Abusive head trauma (AHT), used to be named shaken baby syndrome, is an injury to the skull and intracranial components of a baby or child younger than 5 years due to violent shaking and/or abrupt impact. It is a worldwide leading cause of fatal head injuries in children under 2 years. The mechanism of AHT includes shaking as well as impact, crushing or their various combinations through acceleration, deceleration and rotational force. The diagnosis of AHT should be based on the existence of multiple component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 101 publications
0
32
0
18
Order By: Relevance
“…Regarding why young patients with a low GCS score had a higher mortality risk, it is suspected that it could due to pediatric abusive head trauma (AHT), such as shaken baby syndrome that was observed in severe TBI patients aged ≤ 5 years in this study. One study reported that the mortality of patients with AHT admitted to the Pediatric Intensive Care Unit was 24%; however, AHT is a potentially preventable injury [ 20 ]. Moreover, a previous study showed that mortality in severe TBI patients aged ≥ 65 years was 71–87%, and the mortality increased age-dependently [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding why young patients with a low GCS score had a higher mortality risk, it is suspected that it could due to pediatric abusive head trauma (AHT), such as shaken baby syndrome that was observed in severe TBI patients aged ≤ 5 years in this study. One study reported that the mortality of patients with AHT admitted to the Pediatric Intensive Care Unit was 24%; however, AHT is a potentially preventable injury [ 20 ]. Moreover, a previous study showed that mortality in severe TBI patients aged ≥ 65 years was 71–87%, and the mortality increased age-dependently [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, cases of intentional injury such as abusive head trauma may be included in this study cohort <1 year old. A previous study reported that several cases of child abuse existed among younger paediatric patients who had an injury event at home and that younger paediatric patients with abusive head trauma had higher mortality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hung [11] Pediatric abusive head trauma X Yu et al [12] Injury patterns of child abuse: experience of two level 1 pediatric trauma centers X Mian et al [13] Shaken baby syndrome: A review X Schelhorn et al [14] Intracranial hemorrhage detection over time using susceptibility-weighted magnetic resonance imaging X Adamsbaum et al [15] Dating the abusive head trauma episode and perpetrator statements: Key points for imaging X X Wootton-Gorges et al [16] ACR appropriateness criteria ® suspected physical abuse-child X X Maguire et al [17] Retinal haemorrhages and related findings in abusive and non-abusive head trauma: A systematic review X X Vinchon et al [18] Confessed abuse versus witnessed accidents in infants: Comparison of clinical, radiological, and ophthalmological data in corroborated cases X Binenbaum et al [19] Retinal hemorrhage and brain injury patterns on diffusion-weighted magnetic resonance imaging in children with head trauma X X Christian et al [20] The eye examination in the evaluation of child abuse X Binenbaum et al [21] Patterns of retinal hemorrhage associated with increased intracranial pressure in children X Bhardwaj et al [22] A systematic review of the diagnostic accuracy of ocular signs in pediatric abusive head trauma X Choudhary et al [23] Consensus statement on abusive head trauma in infants and young children X Elinder et al [24] Traumatic shaking: The role of the triad in medical investigations of suspected traumatic shaking X Bradford et al [25] Serial neuroimaging in infants with abusive head trauma: Timing abusive injuries X X Agrawal et al [26] Prevalence of retinal hemorrhages in critically ill children X Gekat et al [27] SDH and EDH in children up to 18 years of age-A clinical collective in the view of forensic consideration X X Zuccoli et al [28] Susceptibility weighted imaging depicts retinal hemorrhages in abusive head trauma X Mulvihil et al [29] An inter-observer and intra-observer study of a classification of RetCam images of retinal haemorrhages in children…”
Section: Ophthalmologic Evaluation All Itemsmentioning
confidence: 99%